2014
DOI: 10.1111/trf.12972
|View full text |Cite
|
Sign up to set email alerts
|

Prospective surveillance of D− recipients of D+ apheresis platelets: alloimmunization against D is not detected

Abstract: Prospective surveillance confirms prior retrospective observations that D- patients do not appear to risk D alloimmunization after receiving D+ apheresis PLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
(52 reference statements)
3
10
1
Order By: Relevance
“…In the present study, out of 332 D‐negative patients received D‐positive platelets who were analysed for the formation of anti‐D, only three patients developed anti‐D. This rate of 0·9% alloimmunization was similar to many recent published studies .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, out of 332 D‐negative patients received D‐positive platelets who were analysed for the formation of anti‐D, only three patients developed anti‐D. This rate of 0·9% alloimmunization was similar to many recent published studies .…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Table , studies employing only SDPC did not have any alloimmunization . Alloimmunization was observed in studies employing both RDPCs and SDPCs or in studies using only RDPCs.…”
Section: Discussioncontrasting
confidence: 55%
“…It can therefore be deduced that PC from apheresis have a lower risk of producing anti-D alloimmunization. This statement is supported by the literature: in none of the studies in which patients were transfused only with PC from a single-donor apheresis, anti-D alloimmunization was detected [6,21,24,25]. These data suggest that anti-D immunoprophylaxis is not necessary in RhD-negative patients receiving exclusively RhD-positive apheresis PC.…”
Section: Discussionsupporting
confidence: 76%
“…Earlier studies reported the incidence of D alloimmunization in D-negative recipients of D-positive PC transfusions to be up to 19% [3,14,15,16,17,18]; more recent studies revealed lower frequencies of 0-7% [19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%